The Ten Roads to Riches : The Way the Wealthy Got There (And How You Can Too!) - Fisher, Kenneth L. and Hoffmans, Lara (Hoboken John Wiley and Sons, 2009)
Have you ever wondered how the super-rich built their wealth--and whether you could do it the same way? Surprisingly, the super-wealthy usually get there by taking just one of ten possible roads. And now, so can you! The Ten Roads to Riches teaches you how to build wealth by following the same successful paths others have used. Renowned investment expert and self-made billionaire Ken Fisher tells you how to increase your chances of success
Include Notes and Index
Keywords: Wealth -- Success in business -- Success